Psychological Intervention in Community-Based Treatment of Schizophrenia: a Systematic Narrative Review - Osi Kusuma Sari; Subandi Subandi (Universitas Ahmad Dahlan, 2021)
Add psychological interventions based mental health services community for treating people with schizophrenia (ODS) can provide positive opportunities in the recovery process. However, there was no systematic literature review for this yet. This article aims to identify and synthesize ODS's psychological interventions in the community to portray held various interventions. A systematic narrative review with the procedure of PRISMA was used in this research. The inclusion criteria are 1) psychological intervention; 2) involvement of a psychologist; 3) community settings. The search was carried out from April- May 2020. Out of 103 journals, 72 journals were reviewed, and a total of 7 journals were analyzed in this study. The involvement of psychologists in crucial positions in community mental health services is rare. Most of the interventions are led by psychiatrists. Psychological interventions include psychoeducation, CBT, SST, social support therapy, and online psychotherapy with